Preference for Reinforcers Under Progressive- and Fixed-Ratio Schedules: A Comparison of Single and Concurrent Arrangements - Glover, Ashley C (The Society for the Experimental Analysis of Behavior, 2008)
Progressive-ratio (PR) schedules were used to identify the break point (i.e., the last schedule value completed) for 2 reinforcers under single and concurrent schedules. After the respective break points were established, the same reinforcers were presented under concurrent fixed-ratio (FR) schedules that were yoked to the break points obtained with the PR schedules. Results suggested that the participants responded more for the high-preference item than for the low-preference item, regardless of the presentation arrangement (single or concurrent presentations). This pattern of responding was maintained when the reinforcers were presented under dissimilar FR schedules. The results suggest that responding for differentially preferred stimuli may vary as a function of differences in schedule requirements.